Management of Anemia A Comprehensive Guide for Clinicians (Springer New York, 2018)
This concise and practical resource brings together recent advances in identifying and managing anemia of chronic disease (inflammation), genetically related anemia and anemia related to chronic end organ damage. Chapters provide a detailed analysis of the current science of anemia, approaches to different patient populations, comorbid conditions and nutritional aspects of anemia. Novel therapies focused on physiological pathways are introduced and discussed. Controversies from the perspective of subspecialists focused in treating major causes of anemia within their specific disciplines are also presented. Easy-to-reference and authored by experts in each clinical scenario, Management of Anemia is the launching point for learning more about this challenging and common condition.